Proportion Dependent Mixing Effects of CaCO3 in Natural Waters - Hui, Qian; Peiyue, Li (Asian Journal of Chemistry, 2012)
An interesting phenomenon named proportion dependent mixing effect of CaCO3 in natural waters was discovered and discussed. The proportion dependent mixing effect is defined as mixing corrosion occurring in some of the mixing ratios and mixing precipitation in other ratios when two solutions are mixed. The interesting phenomenon can be produced by mixing of two unsaturated water samples (with respect to CaCO3), two supersaturated water samples or mixing by an unsaturated sample and an oversaturated sample. The proportion dependent mixing effects usually occur under the following conditions: (1) the HCO3– concentration in one end member solution is much higher than that in the other solution and the concentration of Ca2+ in the former aqueous solution is much lower than that in the latter one; (2) pH value in the higher HCO3– concentration solution is higher than that in the lower HCO3– concentration solution.